Hubungan suhu rumah dan kontak penderita dengan kejadian penularan tuberkulosis di Kecamatan Manonjaya Kabupaten Tasikmalaya - Dewi, Candrawati Puspita; Raharjo , Mursid; Adi , Mateus Sakundarno (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Based on data from the Global Tuberculosis Report, the World Health Organization (WHO) in 2021 states that from 7.1 million in 2019 to 5.8 million in 2020, a 17% decrease, around 16 countries contributing to this decrease, namely India, Indonesia, the Philippines, were affected. worst. Reduced access to TB diagnosis and treatment has resulted in an increase in TB deaths, estimated at 1.3 million TB deaths in 2020. TB cases in Tasikmalaya Regency are still 45% and there are 36% RO TB cases (43 people) and the discovery of TB suspects has also not yet reached the target, which is only 40%. The aim of the research was to determine the relationship between house temperature and patient contact with the incidence of tuberculosis in Manonjaya District, Tasikmalaya Regency. The research design used case control. The research was conducted in March 2024 in Manonjaya District, Tasikmalaya Regency. The research sample was 128 respondents. The independent variables are the temperature of the house and the patient's contact. The dependent variable is the incidence of pulmonary tuberculosis transmission. The instrument is an observation sheet. Data were analyzed by chi square test using SPSS. This research applies the principles of confidentiality, useful information and scientific development. The results of the study showed that there was a relationship between house temperature (OR=2.15; 95% CI; 1.05-4.37) and patient contact (OR=4.31; 95% CI; 2.04-9.11) with the incidence of transmission of tuberculosis in the home. The conclusion is that there is a relationship between house temperature and patient contact with the incidence of tuberculosis in Manonjaya District, Tasikmalaya Regency. Tuberculosis sufferers and the patient's family can take preventive measures to prevent transmission of tuberculosis.